Sequential Nitrification—Autotrophic Denitrification Using Sulfur as an Electron Donor and Chilean Zeolite as Microbial Support - Huilinir-Curio, C (Multidisciplinary Digital Publishing Institute (MDPI), 2023)
Sequential nitrification–autotrophic denitrification (SNaD) was carried out for ammonium removal in synthetic wastewater (SWW) using sulfur as an electron donor in denitrification. Four reactors were operated in batch mode, two with zeolite (1 mm size) used as microbial support and two without support, to assess the effect of the zeolite addition in the SNaD. Aeration, anoxic, and anaerobic cycles were established, where 96% removal of NH4+-N (oxidized to nitrite or nitrate) was achieved in nitrification, along with 93% removal of NO3−-N in denitrification for the SNaD with zeolite. It was observed that the use of zeolite assists in buffering reactor load changes. Inhibition caused by nitrite accumulation in the denitrification stage was minimized by increasing the nitrogen concentration in the SWW. The results obtained in this study are the basis for the development of ammonium removal by simultaneous nitrification–autotrophic denitrification using a single reactor. © 2022 by the authors.